The morphosynctactic and lexical aspects of spanglish in a spanish as a second language lesson in a university setting - Tugues Rodríguez, Cristian (Universidade Estadual Paulista, 2019)
This research focuses on the justification of bringing the linguistic contact into second language classrooms. In particular, we show our own experience by taking Spanglish from the United States into a Spanish as a foreign language (E/LE) lesson within a university setting. Therefore, to carry out this, we offer a lesson planning where the student is able to learn about this so called popular American Spanish at the same time we teach the different mechanisms and linguistic resources that form it so as to classify some real and literary samples in lexicographic charts. Thus, we intend to bring not only the linguistic and panhispanic varieties to our E/LE lesson, but also the conception in the classroom that languages are something global in a continuous evolution.